2007
DOI: 10.1016/j.socscimed.2007.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Covariations of emotional states and alcohol consumption: Evidence from 2 years of daily data collection

Abstract: We examined inter-and intra-individual covariations of mood and alcohol consumption in a sample of 171 light, medium, and heavy alcohol consumers aged 21 and over who reported daily about drinking and mood for a period of up to 2 years. The sample was recruited by advertisements in local newspapers and referral from former respondents in Northern Vermont, USA, between July 1997 and September 2000. Participants reported daily alcohol consumption and mood via Interactive Voice Response (IVR) technology. Within-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 48 publications
2
46
1
Order By: Relevance
“…This association occurred even though participants reported no drug misuse at enrollment and infrequent drug use during the IVR interval. Greater drinking also was associated with weekends compared with weekdays, as found in prior IVR studies (e.g., Schroder and Perrine, 2007). These results provide further evidence of the co-occurring negative effects of multiple behavioral and environmental risk factors on the temporal patterning of substance use.…”
Section: Discussionsupporting
confidence: 83%
“…This association occurred even though participants reported no drug misuse at enrollment and infrequent drug use during the IVR interval. Greater drinking also was associated with weekends compared with weekdays, as found in prior IVR studies (e.g., Schroder and Perrine, 2007). These results provide further evidence of the co-occurring negative effects of multiple behavioral and environmental risk factors on the temporal patterning of substance use.…”
Section: Discussionsupporting
confidence: 83%
“…In terms of dropout, only about 33 participants (75%) of the original sample were retained until the end of the 90-day self-reporting period. In comparison, similar IVR-based studies in alcohol research reported completer rates higher than 90% over self-reporting periods of up to 2 years [5,6]. Potential reasons for the differences in the completer rates may include 1) the greater sensitivity of sexual behavior self-reports; 2) lower risk perceptions or lower perceived relevance of the study questions among healthy college students; 3) stricter rules for bonus payments if calls were missed; and 4) differences in the ethnic composition of the samples.…”
Section: Feasibility Studies In Hiv-risk Populationsmentioning
confidence: 69%
“…IVR can be used for computer-assisted screening of a population [1] or in-depth daily assessments of risk behaviors [2••, [3][4][5][6]. It can be used as an external memory to promote participants' medication adherence [7] or used as a medium to relay health messages or advice intended to improve health behaviors [1].…”
Section: Utility Of Ivr As a Research Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of nonimaging human studies have attempted to experimentally alter emotional states while administering alcohol or measuring alcohol intake (Gabel et al, 1980;Stritzke et al, 1996;Curtin et al, 1998;Schroder and Perrine, 2007), but these studies have not demonstrated a specific anxiolytic interaction between alcohol and emotional cues. Alco- Figure 2.…”
Section: The Anxiolytic Effect Of Alcohol In Visual-emotional Brain Amentioning
confidence: 99%